2018
DOI: 10.1007/s00056-018-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional skeletal, dentoalveolar and temporomandibular joint changes produced by Twin Block functional appliance

Abstract: Treatment with the Twin Block functional appliance results in significant skeletal, dentoalveolar, and condylar changes in both dimensions and positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 32 publications
17
64
0
Order By: Relevance
“…Two studies reported changes of condylar dimensions. [5,15] Because Elfeky et al reported both left and right condylar changes after treatment, we extracted data of both sides as well for meta-analysis.…”
Section: Synthesized Results Of Treatment Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported changes of condylar dimensions. [5,15] Because Elfeky et al reported both left and right condylar changes after treatment, we extracted data of both sides as well for meta-analysis.…”
Section: Synthesized Results Of Treatment Effectsmentioning
confidence: 99%
“…Two studies reported the effects of Twin-block appliance on the anterior, superior and posterior joint space. [5,15] We also extracted data of both sides of patients in Elfeky's study for this metaanalysis.The meta-analysis revealed that there was no significant change in the anterior joint space (mean difference: -0.15mm; 95%CI: -0.48 to 0.19mm; P=0.39; I²=68%). However, superior joint space increased with statistically significance (mean difference: 0.70mm; 95%CI: 0.43 to 0.97mm; P<0.00001; I²=0%), as well as posterior joint space (mean difference: 0.29mm; 95%CI: 0.03 to 0.56mm; P=0.03; I²=0%) (Fig 3).…”
Section: Synthesized Results Of Treatment Effectsmentioning
confidence: 99%
See 3 more Smart Citations